Combating Stunting Through Cultural Heritage: A Study on Community Health Workers’ Knowledge in Klaten, Indonesia - Sumardino Sumardino; Fina Mahardini; Sudiro Sudiro; Sugiyarto Sugiyarto (GLOBAL HEALTH SCIENCE GROUP, 2026)
Stunting remains a major public health concern in Indonesia, with long-term implications for child development and national productivity. Community health workers (CHWs) play a key role in promoting and preventing stunting at the community level. Cultural traditions such as bancaan, a Javanese communal gathering, present unique opportunities to convey health messages in a culturally resonant manner. This study aimed to assess the level of knowledge among CHWs regarding stunting prevention, both from biomedical and local wisdom perspectives, with particular attention to the bancaan tradition. A quantitative, cross-sectional study was conducted involving 53 CHWs in the working area of Ceper Primary Health Center, Klaten Regency, selected through total sampling. A validated structured questionnaire was employed, and data were analyzed descriptively. The majority of CHWs (84.9%) demonstrated a high level of knowledge concerning stunting prevention, including awareness of bancaan as a culturally rooted educational medium. CHWs in the study area possess strong knowledge of both biomedical and cultural approaches to stunting prevention. Integrating local traditions such as bancaan into CHW training and community health interventions is recommended to enhance the cultural relevance and effectiveness of public health messaging